Etika Berbangsa dan Bernegara melalui Peran Bahasa dalam Kajian Analisis Ilmu Antropologi - Nugroho Trisnu Brata (Unisia, 2007)
This paper explains about language function with functionalism approach. In general eth- nic group is known as a tribe or community with the same identity or tradition. Identity of the ethnic group includes patterns of kinship, marital, religion, home architecture, settle- ment, language etc. Language is one of the identity and becomes a collective identity of ethnic. But language can be a nation identity not just an ethnic identity. One of the charac- teristic of Indonesia is Bahasa Indonesia as a national identity or national language. The mass media like television broadcasting (TVRI and private TV) are the important channels to promote the socialization of using Bahasa Indonesia correctly. Key words: language, function, integration, identity